ISSUES OF CRIMINAL LIABILITY FOR VIOLATION OF LEGISLATION ON PERSONAL DATA IN SOME FOREIGN COUNTRIES ANNOTATION - Choriev Anvar Kuzievich (International Journal of Business, Law and Political Science, 2025)
Objective: This article aims to analyze the criminal liability mechanisms for violations of personal data protection laws across several foreign jurisdictions, comparing them with the legal framework in Uzbekistan. Method: A comparative legal analysis was conducted, examining statutory regulations, case law, and institutional practices in countries such as Belarus, Kazakhstan, the United Kingdom, and Japan. Results: The findings indicate that while Belarus and Kazakhstan have criminal provisions similar to Uzbekistan’s legal system, other countries adopt divergent approaches. For instance, the United Kingdom imposes criminal liability through the Data Protection Act 2018, while Japan emphasizes constitutional and administrative legal instruments without explicit criminal penalties. These disparities highlight the absence of a harmonized global standard for criminal liability in personal data protection. Novelty: This study provides a detailed comparative perspective on the diversity of legal mechanisms employed globally to address personal data violations and underscores the need for Uzbekistan to modernize and harmonize its criminal law framework in line with international best practices, without compromising its legislative sovereignty.